Ultrasonographic criteria for ectopic pregnancy - Carpio Guzmán, Luis Alberto (2021)
Ectopic pregnancy is a gyneco-obstetric pathology whose management has changed today, going from being a purely surgical management pathology to a medical management entity with surgical indications. Transvaginal ultrasound has revolutionized evaluation in gynecology and in the first trimester of pregnancy, which has allowed the diagnosis of new pathologies.